Frontier Production Functions and Technical Progress: A Study of Teneral Milk Processing in Swedish Dairy Plants - Finn R. Førsund; Lennart Hjalmarsson (The Research Institute of Industrial Economics (IUI), 1977)
Technical change in general milk processing is estimated within a homothetic frontier production function allowing neutrally variable scale elasticity. The results show that technical progress is characterized by a rapid increase in optimal scale and a small capital saving bias, increasing the marginal productivity of labour relative to capital. To characterize technical change, Salter's measures of bias and technical advance are utilized and interpreted within the framework of the efficiency cancepts of Farrell.
Keywords: O13; Q16; 330; Agriculture; Technical progress; Production function